GOVERNMENT SPENDING, TRADE OPENNESS AND ECONOMIC GROWTH IN INDIA: A TIME SERIES ANALYSIS - Hrushikesh Mallick (Centre for Development Studies-WP403, 2008)
The study examines the impact of aggregate government expenditure and its two broader components such as revenue expenditure and capital expenditure on the growth rate of output in the Indian context along with other key potential determinants of economic growth such as trade openness and private investment. It utilizes structural vector autoregression (SVAR) methodology for examining the dynamic response of output growth to the shocks in major macro economic variables wherein public expenditure is considered to be an important fiscal policy instrument. From the empirical analysis, the study finds that neither aggregate expenditure nor the capital expenditure does have significant influence on the growth rate of the economy. Rather, surprisingly, it is the revenue expenditure, to some extent, explains the variation in growth rate and it is again in the positive direction. Besides such relationship between public expenditure and output growth, it is mainly taxes, openness measure and private investment do influence growth rate. Contrary to the expectation, the taxes which should have a negative influence on the growth rate of output, surprisingly has a positive influence but openness measure and private investment have positive impacts in line with general expectation of the theory.